Ecossistema de inovação para contribuir com a sustentabilidade no cooperativismo agropecuário: uma proposta de framework - Schwade, Darlan Eduardo (Universidade do Vale do Rio dos Sinos, 2025)
From a competitive perspective, the integration of technology and innovation is the driving force for new opportunities in the cooperative ecosystem associated with agribusiness. Using the Design Science Research (DSR) methodology, this research proposed a framework to guide the combination of internal and external resources in the innovation ecosystem of agricultural cooperatives, with the aim of generating services capable of increasing the competitiveness of cooperatives. Based on the dynamics of innovation ecosystems and the complementarity of resources and skills, the research showed how these elements can promote additional and appropriate value and results that would not be achieved in isolation by the different actors involved. The results of the research showed how the ecosystem can integrate the innovation actions of the agricultural cooperative system and, through the logic of complementarity, promote sustainability, offering services capable of simultaneously meeting market demands and the internal demands of the cooperative system. The proposed framework reflects an integrated view of the ecosystem, organized into three interdependent subsystems. The innovation, research, technology and extension subsystem, positioned as the central core, has the role of integrating and coordinating the dynamics of the ecosystem, connecting with the internal subsystem (cooperatives and producers) and the external subsystem (market). This integration and interaction between the subsystems enables the exchange of resources and strategic capabilities, which in a complementary manner generate additional value through the services offered. These services are directed both to cooperative members and cooperatives, called S1 services, and to external actors, called S2 services, meeting their respective demands. In other words, transforming resources into services that, through innovation, drive economic growth. Competitiveness thus arises as a result of the effective use of resources, the capacity for adaptation and the expansion of knowledge, promoting an innovative and sustainable environment within the agricultural cooperative ecosystem.
Keywords: Ecossistemas de Inovação; Cooperativismo agropecuário; Recursos estratégicos; Serviços; Competitividade; Innovation ecosystems; Agricultural cooperativism; Strategic resources; Services; Competitiveness; ACCNPQ::Ciências Sociais Aplicadas::Administração